2016
DOI: 10.1186/s12917-017-0947-1
|View full text |Cite
|
Sign up to set email alerts
|

Food-specific sublingual immunotherapy is well tolerated and safe in healthy dogs: a blind, randomized, placebo-controlled study

Abstract: BackgroundFood allergies are increasing in prevalence but no treatment strategies are currently available to cure dogs with food allergy. Over the past decade, experimental food allergen-specific sublingual immunotherapy (FA-SLIT) has emerged as a potential treatment for food allergies in human medicine. However, FA-SLIT has not been investigated in dogs. Therefore, the objective of this study was to prospectively evaluate the safety, tolerability and dispenser sterility of FA-SLIT in healthy dogs before testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Although in these animals little is known about the eliciting specific allergen molecules [ 8 , 9 ], the immune mechanisms relevant for allergies in dog, cat and horses are more similar to humans than any rodent models. These facts prompted experimental approaches including models for food sensitization [ 10 ] or for sublingual allergen-specific immunotherapy [ 11 ], up to clinical comparative investigations in animal patients, which are very similar to humans [ 12 , 13 ]. Technically, however, all investigations in animals are regulated by the animal experimentation directives [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although in these animals little is known about the eliciting specific allergen molecules [ 8 , 9 ], the immune mechanisms relevant for allergies in dog, cat and horses are more similar to humans than any rodent models. These facts prompted experimental approaches including models for food sensitization [ 10 ] or for sublingual allergen-specific immunotherapy [ 11 ], up to clinical comparative investigations in animal patients, which are very similar to humans [ 12 , 13 ]. Technically, however, all investigations in animals are regulated by the animal experimentation directives [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Testing this hypothesis initially in a mouse model using BALB/c mice sensitized with ovalbumin showed that attenuation of allergic responses was seen in mice receiving commercial immune Ig and anti-idiotype Ig of human origin, see Figures 3 and 4. These important observations justified a pilot preclinical trial of this same therapy in a dog model (Beagles) of atopic dermatitis, the most common allergic skin disease in dogs [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 86%
“…Skin, respiratory, and food allergies are not uncommon in dogs, and the immune mechanisms involved are more like humans than in rodents [5,6], making them a favoured species for study [7][8][9][10][11]. Dust mite allergens are thought to be highly relevant to canine allergic responses [12], although skin reactivity and dust mite-specific serum IgE have also been detected in several dogs without clinical signs of allergy, suggesting that sensitization can occur without necessarily inducing clinically significant reactivity [13].…”
Section: Introductionmentioning
confidence: 99%